The Álvarez Encyclopedia: Indoctrinating Resource of an Essentialist National Identity (1945-1964) - González García, Erika (Historia y Memoria de la Educación, 2020)
This article is focused on the identities of peoples, a matter of current relevance, among other reasons because it is linked to the issue of nationalisms. We adopt a uniform and essentialist conception of the being of each people, particularly in dictatorial regimes. This way of conceiving identity is characterized by its consideration of history, ethnic heritage, language, values - considered to be eternal - , together with heroes and their symbols, as the pillars that support it; this is what is called an essentialist identity. We use the three volumes of the Álvarez Encyclopedia as documentary sources. The qualitative methodology used is of a hermeneutical nature, taking into account the contributions of the historical method. The main objective of this research is to reveal what was considered the essence of being Spanish in the Álvarez Encyclopedia, which was the most widely used textbook in the primary schools under the Francoist regime. The textbooks analyzed served as instruments for shaping and conforming children in the ideals of the moment, that is, in national-Catholicism.